Association of sugar-sweetened, artificially sweetened, and unsweetened tea with all-cause and cause-specific mortality: a prospective cohort study in UK biobank - Zhengjun Lin; Min Zeng; Yuqiao Ji; Lifan Wang; Yanlin Wu; Tingting Zhang; Tang Liu (BMC Public Health)
Abstract Although previous observational studies have revealed a significant relationship between tea consumption and reduced mortality risk, the associations of adding sugar or alternative sweeteners to tea with mortality risks are still largely unknown. This study aimed to evaluate the associations of consumption of unsweetened, sugar-sweetened, and artificially sweetened tea with all-cause and cause-specific mortality. A total of 180,344 participants in the UK Biobank were eligible for this study. Data for dietary consumption of unsweetened, sugar-sweetened, and artificially sweetened tea by a 24-hour dietary assessment tool were acquired. During a median follow-up of 11.7 years, 6809 deaths were recorded. Cox models with cubic splines showed significant associations between unsweetened and sugar-sweetened tea and lower all-cause mortality [HRs (95%CI), 0.78 (0.73–0.83)]. Unsweetened tea consumers also had lower risks for cancer and cardiovascular disease (CVD) mortality with the respective HRs (95%CI) of 0.81 (0.74–0.88) and 0.74 (0.64–0.86). The relationship between artificially sweetened tea and mortality risks was inconclusive. Furthermore, more amounts of sugar or alternative sweeteners added to tea may impact the association with mortality. Our findings highlighted that moderate intake of unsweetened and sugar-sweetened tea was associated with lower mortality risks.